Pengembangan E-Modul Berbasis Pemecahan Masalah Pada Materi Larutan Elektrolit dan Non-Elektrolit (ELNOEL) - Ratna Sari Siti Aisyah; Solfarina Solfarina; Unita Yuliantika (Hydrogen: Jurnal Kependidikan Kimia, 2021)
High school students have difficulty in understanding “electrolyte and non-electrolyte” solution materials because they are mostly abstract. Students should study three aspects in electrolyte and non-electrolyte solutions including macroscopic, symbolic and submicroscopic. However, the fact that in school only accentuates macroscopic and symbolic levels. Then the learning resources cannot provide an explanation of the submicroscopic level and the learning model used does not make students active in accordance with the 2013 curriculum. This study aims to produce products in the form of problem solving-based Elnoel E-modules on electrolyte and non-electrolyte solution materials, as well as explaining the feasibility of E-elnoel module and student response to Elnoel E-module. This research is designed with ADDIE model with analyze, design, development, implementation and evaluation stages. This Elnoel e-module is validated by 7 experts (judment) that the results of material validation and media validation are declared valid with a value of 0.85 and 0.81. Then the Elnoel E-module was implemented to 9 students of grade XI science at Al-Qudwah Integrated High School to find out the student's response to the media developed by obtaining a percentage of 89% that belongs to the category very good.It can be seen that the development of media arranged based on problem solving can stimulate students’ thinking skills and get a positive response from students.